MARKETING EVOLUTION: FROM TRADITIONAL TO WEB 3.0 - Andriy Melnyk (Baltic Journal of Economic Studies)
This study analyses the evolution of marketing from conventional techniques to the decentralised, user-driven environment of Web 3.0. The aim is to highlight the changes in marketing strategies brought about by breakthroughs in digital technologies, focusing mainly on the influence of blockchain, AI and decentralised platforms in changing consumer behaviour and business processes. Methodology. The present study employs a comparative analysis methodology, juxtaposing the conventional marketing mix with digital and Web 3.0 marketing components. Integrating qualitative and quantitative data from current literature, case studies, and empirical research, this study explores the application of digital marketing technologies and Web 3.0 techniques across industries. The results obtained demonstrate a substantial transition in marketing methodologies from unidirectional communication in conventional marketing to dynamic, interactive customer interaction in digital and Web 3.0 marketing. The advent of Web 3.0 technologies, including blockchain, tokenization, and decentralized applications, has engendered novel options for individualized, trust-centric interactions between customers and marketers. Furthermore, the empowerment of customers through data management and AI-driven personalisation is identified as a pivotal factor in shaping emerging marketing methodologies. Practical implications. To remain competitive, companies must adapt to the changing digital landscape by adopting Web 3.0 technologies. This includes implementing decentralised models, prioritising data protection and using AI for tailored marketing. Marketers must be equipped to interact with tech-savvy consumers and hybrid AI-based decision-making systems to foster trust and improve the customer experience. Value / Originality. The paper enhances understanding of the transformative impact of Web 3.0 on marketing, providing in-depth analysis of its impact on consumer behaviour and strategic planning. It provides essential insights for marketers seeking to navigate the rapidly evolving digital environment and capitalise on emerging trends.